School meals workers, 1998 (1998)
1998 1960-2000 "School meals workers, 1998" [EP0198], 1998 The front cover of Unison Magazine for April-May 1998 shows catering staff at Southlands Lower School in Bedfordshire celebrating after a tribunal ruled that staff had been underpaid for nearly 4 years. The Union argued that sex discrimination and equal pay legislation was breached when the women's basic pay and other conditions were cut.